Star wars : revenge of the Sith - Stover, Matthew Woodring; Lucas, George, 1944- (London : Arrow, 2004)
Obi-Wan sets out on a dangerous mission to destroy the dreaded Separatist military leader, General Grievous, while Supreme Chancellor Palpatine continues to turn the public against the Jedi and lead Anakin Skywalker to the Dark Side.
"Lucas books.".
Adult
Keywords: Kenobi, Obi-Wan (Fictitious character) -- Fiction; Life on other planets -- Fiction; Space warfare -- Fiction; Vader, Darth (Fictitious character) -- Fiction; Kenobi, Obi-Wan (Fictional character) -- Fiction; Life on other planets -- Fiction; Science fiction; Space warfare -- Fiction; Vader, Darth (Fictional character) -- Fiction